The use and efficacy of intra-operative stress tests in supination-external rotation IV ankle fracture fixation. Issue 1 (February 2015) - Gill, Sarah L.; Behman, Amy; Cochrane, Lynda A.; Love, Gavin J.
Abstract This study examines stress radiograph use in SER IV ankle fracture fixation; the efficacy of external rotation (ERST) and lateral hook (LHST) stress tests with incidence of subsequent fixation failure secondary to syndesmotic diastasis. 154 skeletally mature patients were admitted to our unit with ankle fractures in 12 months. 42 non-SER fractures and 32 SER fractures treated without ORIF were excluded, as were 14 which featured a syndesmotic screw in the primary ORIF. The remaining 66 SER IV fixations were included in the final sample (17 men, 49 women; median age 49 years). No stress test was performed in 51.5% of cases without a single subsequent failure in these fixations. ERST was the more commonly performed test (incidence 30.3%); negative predictive value (NPV) 0.95. Incidence of LHST was 18.2%; NPV 0.83. Both tests were performed in 6.1% of cases; NPV 0.75. The incidence of failure secondary to syndesmotic diastasis was 6.1% (4/66). Notably, there were no failures in the cases where no stress test was performed. Use of either or both external rotation and lateral hook stress tests resulted in failures to detect syndesmotic diastasis with consequent failure of fixation. This study suggests that syndesmotic injuries are not missed due to an absence of a stress test but that stress tests are not sufficiently sensitive or correctly interpreted. Clinical judgement in cases where syndesmotic injury is not present appears accurate. If syndesmotic injury is clinically suspected, apply caution and insert a syndesmotic screw rather than relying on stress test results.